PROSPEK WISATA RELIGI MAKAM KI BUYUT TERIK DALAM MENIGKATKAN PELUANG UMKM DESA TLEMANG NGIMBANG LAMONGAN - Annis Rahmawati; intan mayasari; agus setiawan (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Tourism is one of the major industries that has considerable potential to improve the economy and people's welfare. The existence of MSMEs around tourist destinations provides promising business opportunities, especially in the production and sale of various types of traditional chips which are the flagship products of Tlemang village. This research uses a qualitative approach as a research method with a descriptive approach. The data sources used are primary and secondary data. The results showed that religious tourism at the tomb of Ki Buyut Terik has great potential in improving the economy of Tlemang village through the development of MSMEs. Traditional chip products from the village are an attraction for tourists, and with the application of information technology and digital marketing, as well as innovations in packaging and product diversification, MSMEs can continue to grow and contribute to the local economy. The development of MSMEs in the tourism sector also plays a role in maintaining local cultural identity and religious tradition wisdom, as well as providing wider benefits for the people of Tlemang village. Thus, strategic steps taken by the government, local stakeholders, and MSME actors can strengthen the religious tourism potential of Ki Buyut Terik's tomb in facing the challenges of globalization and social change, as well as create sustainable development for Tlemang village and its surroundings.